Pengembangan Media Permainan Kartu Gambar Dengan Teknik Think Pair Share Pada Siswa Kelas 3 Sekolah Dasar Di Palopo - Yuni Faryanti Sukri; Farida Indriani (Publikasi Pendidikan, 2017)
This study aims to: 1) determine the feasibility ofpicture card game media in with a think pair share techniques, and 2) determine the effectiveness of picture card game media to the learning with a think pair share techniques for grade 3 students of MI DDI I Palopo City. The type of this research is the research and development (R&D). Development is donereferring to Dick & Carey model of development through 9 stages. The stagesinclude Identifying Instructional Goals, Conducting Instructional Analysis, Analyzing Learners and Context, Writing Performance Objectives, Developing Assessment Instruments, Developing Instructional Strategy, Developing and Selecting Instructional Materials, Designing and Conducting Formative Evaluation of Instructional, and Revising Instruction. Validation products involves 1 media expert lecturer, 1 lecture rmatter expert, 2 practitioners, and 2 colleagues. The subjects of the research trial were grade 3 students of MI DDI I Palopo City 2017/2018 school year consisting of 9 students on a small group test and 29 students on a large group test. The instruments used are the interview guide, feasibility assessment sheets picture card game media, and observation sheets. Data collection techniques used are interview techniques, product assessment, and observation. Techniques of data analysis used descriptive analysis, paired samplest test for the effective nessand use of the score conversion to thequalitative data for practicality. The results of one to one trial from experts, practitioners, and colleagues showed picture card game media with make a match techniques of learning fit for use with “excellent category”. Small group trial get positive response as “good criteria”. Large group trial tested effectiveness and product-used practicality. Effectiveness in terms of the result of student’s learning show different mean from 81.23 becomes 95.40. There is increased result of student’slearning showing significance value 0.001 with significance level 0.005.   Practicality of media-used based on teacher’s observation results obtained percentage of95% andthe observation ofthe students obtained 88.75%, respectively with the same practicality criteria, namely"highly practical".